Diversidade e prospecção de bactérias endofíticas degradadoras de petróleo isoladas de macrófitas (Eichhornia spp.) da Região de Santarém-PA - MASCARENHAS, Carla dos Santos (Universidade Federal do Oeste do Pará, 2024)
The association of plants with microorganisms that have endophytic capacity gives the plant some advantages and functions related to secondary metabolism, allowing defense and other important functions for development and survival. This ecological relationship extends to aquatic species as well, such as the macrophytes of the genus Eichhornia Kunth, which act in bioremediation processes and in the ecological balance, with efficiency in the purification of areas contaminated by thermotolerant coliforms. In view of this purifying action and the potential of endophytic microorganisms from these plants, the present study aimed to isolate, characterize and test the potential of endophytic bacteria from aquatic macrophytes (Eichhornia spp.) to degrade hydrocarbons. For this, collections of Eichhornia spp. in Lago do Maicá and Bosque Vera Paz, both in Santarém, Pará, during the seasonal periods (flood, full and ebb) of the Tapajós River, between the months of January and August 2022, the time of greatest occurrence of macrophytes. To obtain the endophytic microorganisms, leaf, stem, bulb and root fragments of the plant were cut and inoculated in Petri dishes (90 mm) containing 20mL of culture medium for bacterial growth. The identification of isolates was performed by means of biochemical tests. The degradation test of petroleum derivatives was carried out with the Agar + Petroleum 0.5% medium. 126 strains of cultivable endophytic bacteria were obtained in the two areas studied, with the genera Clostridium and Corynebacterium being the most frequent in the samples, being present in all parts of the plant and in the two areas sampled, the other genera were: Shigella, Serratia, Enterobacter, Klebisiella, Pseudomonas, Staphylococcus and Mycobacterium. In comparison between the seasonal periods, the statistical tests did not show significant differences. The genus Corynebacterium had the highest number of isolated strains, these having the ability to degrade hydrocarbons. In view of the results obtained, it is concluded that aquatic macrophytes of the genus Eichhornia have a large community of endophytic bacteria, some of which have the potential for bioremediation of petroleum derivatives, requiring future research to bioprospect this microbial biodiversity and contribute to the mitigation of environmental problems in the ports of Santarenos.